Countinous Running With Smartphone Application: Peningkatan Vo2Max pada Pemain Bola Basket - Faozi, Faiz; Hidayatulloh, Dede Taufik; Nugraha, Tarsyad; Bahri, M Syamsul; Sundari, Sri; Cahyani, Olivia Dwi (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The purpose of this research study is to determine the impact of Countinuous Running training based on the Nike Running Club application in increasing Vo2Max in the STKIP Bina Mutiara Student Activity Unit. The research method applied in this study ia an experiment with a Ome Group Pre-test Post-test Design. The measurig instrumen used is the Balke Test to assess Vo2Max. The research subject in this study were 20 students involved in the basketball UKM selected through a satuarted sample method. Data analysis show an increase in Vo2Max or endurance in basletball players after being given treatment using Countinuous Running training based on the Nike Running Club application, with a value of t=45.987 and sig=0.000<0.05, indicating a significant effect with an average pre-test of 43.27 and an average post-test of 47.24. Based on these finding, it can be concluded that there is an increas in Vo2Max by using Countinuous Running training based on the Nike Running Club application in basketball players.